Prophylactic oophorectomy in pre-menopausal women and long term health – a review - Shuster, Lynne T. (2008)
OBJECTIVE: To review the data on long-term outcomes in women who underwent prophylactic bilateral oophorectomy, a common surgical procedure that has more than doubled in frequency since the 1960s. STUDY DESIGN: Literature review of published data on consequences of prophylactic bilateral oophorectomy. Special emphasis was given to the Mayo Clinic Cohort Study of Oophorectomy and Aging. MAIN OUTCOME MEASURES: Overall mortality, cardiovascular disease, cognitive impairment and dementia, parkinsonism, osteoporosis, psychological well-being, and sexual function. RESULTS: There is a growing body of evidence suggesting that the premature loss of ovarian function caused by bilateral oophorectomy performed before natural menopause is associated with several negative outcomes. In particular, studies have revealed an increased risk of premature death, cardiovascular disease, cognitive impairment or dementia, parkinsonism, osteoporosis and bone fractures, decline in psychological well-being, and decline in sexual function. The effects involve different organs (e.g., heart, bone, or brain), and different functions within organs (e.g., cognitive, motor, or emotional brain functions). Estrogen treatment may prevent some of these negative outcomes, but not all. CONCLUSION: The potential adverse effects of prophylactic bilateral oophorectomy on heart health, neurologic health, bone health, and quality of life should be carefully weighed against its potential benefits for cancer risk reduction in women at average risk of ovarian cancer.